Fabrication of AlN/Cu Composites Using Electroless Plating and Evaluation of Their Thermal Properties according to AlN Particle Size - Cho, Sung Chul; Ko, Se-Hyun; Kim, Hye Sung; Ahn, Jae-Pyung; Han, Jun Hyun (KOREAN INST METALS MATERIALS, 2015)
AlN/Cu composite powders with a core-shell structure were synthesized by a new technique using electroless plating of Cu on AlN particles and consolidated by spark plasma sintering (SPS). Dependence of the thermal conductivity and coefficient of thermal expansion (CTE) of the AlN/Cu composites on the particle size of AlN were studied. The thermal conductivity and coefficient of thermal expansion were significantly dependent on the existence of both boundary pores surrounding the Cu-coated AlN particles and the internal pores of the AlN particles. In order to eliminate the pores, the temperature and pressure of SPS were increased and the lIN particles were heat-treated at high temperature. Adoption of the core-shell AlN/Cu composite powders facilitated the fabrication of AlN/Cu composites with low porosity and uniform distribution in the AlN in Cu matrix.